Pushing the boundaries on mentoring: Can mentoring be a knowledge tool? - Henriques, Paulo Lopes; Curado, Carla (Journal of Business Economics and Management, 2009)
Easy access to organizational knowledge is fundamental in dynamic environments that demand continuous firm adaptation. In that scenario we believe that mentors have a key role as access facilitators to knowledge in the change periods. We have developed this study aiming to explore the role and importance of mentors as knowledge access facilitators. We have approached that role in two different ways. We set apart the knowledge base in two categories: Information centers and organizational memory, accepting that mentors act differently accordingly. Based on the literature reviewed we were able to stage a three‐dimensional theoretical setting (mentoring, knowledge, and change) and produce three research questions. We have addressed these research questions using an exploratory qualitative approach to five different firms from three industries apart. This study contributes to the literature at least in two ways. Firstly, it connects the mentor figure to the knowledge base's access, exposing the importance of the mentor as a knowledge access facilitator during change periods. Secondly, by categorizing the knowledge base in two different ways, we are able to explicitly differentiate mentor roles accordingly.First Publish Online: 14 Oct 2010